Top Management Teams Diversity and Firm Performance : The Moderating Impact of Chief Digitalization Officer and Board Size in Swiss and German Corporations - Velinov, Emil (2025)
The subject of the habilitation is meticulously focused on the exploration of top management teams diversity and its consequential impact on firm performance, particularly emphasizing the characteristics of executives in the digital epoch of the twenty-first century. This work serves as a progressive continuation of the author’s doctoral thesis (Velinov, 2014), concentrated on the intricate interrelations between the firm life cycle and the socio-economic antecedents on the upper echelons within Czech, Swiss, and German corporations. Within the habilitation, nuanced emphasis was placed on specific board characteristics, including gender, age, and nationality, analyzed within the developmental context of organizations. Between 2018 and 2022, the author has contributed a myriad of publications to peer-reviewed international journals and conferences, primarily within the research domain of top management team diversity. In the period 2019-2023, collaborative research endeavors were undertaken focusing on managerial practices and diversity and inclusion initiatives within German and Czech firms, facilitated under the Bavarian-Czech Universities Agency (BTHA). The fundamental aim of this habilitation is to investigate the influence of selected characteristics of top management teams, such as dominant function, team tenure, and international experience, on firm performance amidst the fourth industrial revolution and digitalization. The work employs quantitative research methodologies, utilizing a data panel spanning from 2018 to 2022 to scrutinize top management team diversity and the emerging role of Chief Digitalization Officer in driving firm performance within various flagship firms in Switzerland and Germany.